CHEMOSTRATIGRAPHY OF THE JURASSIC SYSTEM: APPLICATIONS, LIMITATIONS AND IMPLICATIONS FOR PALAEOCEANOGRAPHY - Jenkyns H.C.; Jones C.E.; Gröcke D.R.; Hesselbo S.P.; Parkinson D.N. (My University, 2002)
Current chemostratigraphical studies of the Jurassic System primarily involve the use of one sedimentary component (marine organic carbon), one divalent transition metal substituted in carbonate (manganese), and two isotopic tracers: strontium-isotope ratios (87Sr/86Sr) and carbon-isotope ratios (13Ccarb and 13Corg) in carbonate and in organic matter. Other parameters such as Mg/Ca and Sr/Ca ratios in calcite, oxygen-isotope ratios (18O) in carbonate, sulphur-isotope ratios (34S) in carbonate-hosted sulphate, nitrogen-isotope ratios (15Norg) in organic matter, osmium-isotope ratios (187Os/188Os) in black shales and neodymium-isotope ratios (143Nd/144Nd) in various mineral phases are also useful but at present give poor resolution because the database is incomplete or compromised by various factors. Stratigraphical patterns in total organic carbon (TOC) can be of either local or regional significance, depending on the lateral extent of the former nutrient-rich and productive water mass. Divalent manganese follows a similar pattern, being concentrated, most probably as a very early diagenetic phase, only in oxygen-depleted waters that typically underlie zones of elevated organic productivity. Shifts in Mg/Ca and Sr/Ca ratios on the time scale of ammonite subzones seem largely to reflect temperature changes. Strontium-isotope ratios from pristine skeletal calcite provide a global signal; 13C values from carbonates with minimal diagenetic overprint potentially do the same, although small spatial differences in palaeo-water-mass composition may have been locally significant. Oxygen-isotope determinations on carbonate rocks and fossils generally yield values that are too scattered to be stratigraphically useful, because they reflect palaeotemperature, the evaporation–precipitation balance in sea water and the impact of any diagenesis involving an aqueous phase. Nitrogen-isotope ratios in organic matter reflect the chemistry of ancient water masses as affected by nitrate utilization and denitrification, and the stratigraphical pattern of this parameter is more likely to correlate only on a regional basis. Neodymium-isotope ratios in sea water are also water mass dependent and greatly affected by regional sources and oceanic current systems. Preliminary data on sulphur-isotope ratios in carbonates and osmium-isotope ratios in organic-rich shales, both potentially offering global correlation, indicate that these tracers may be valuable, although the records at present are not sufficiently well established to allow high-resolution regional correlation. In all cases, biostratigraphically well-dated reference sections, against which the relevant geochemical data have been calibrated, are required in the first instance. To date, studies on the stratigraphical distribution of organic carbon have been principally carried out in both northern (Boreal) and southern (Tethyan) Europe; carbon-isotope stratigraphy has been undertaken primarily, but not exclusively, on bulk pelagic sediments from the Alpine–Mediterranean or Tethyan domain; and strontium-isotope stratigraphy has been undertaken largely on calcitic skeletal material (belemnites and oysters) from northern and southern Europe. In many sections, including those containing ammonites, multi-parameter chemostratigraphy can give resolution that exceeds that attainable by classic biostratigraphical means. Strontium-isotope ratios in skeletal calcite are a particularly powerful tool for illustrating changes in sedimentary rate and revealing gaps in the stratigraphical record.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская